1998
DOI: 10.1046/j.1523-5394.1998.006004217.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening of Older Women A Primary Care Issue

Abstract: Barriers for appropriate cancer screening for older women exist for both the provider and the patient; however, many of these obstacles can be overcome. Improving the resident's exposure to the current recommendations, increasing geriatric content in the training program, and initiating a reminder system may reduce some of the provider barriers. The use of midlevel providers may increase the preventive services offered to older women as well as educate and empower these women to become responsible for their ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(47 reference statements)
3
7
0
Order By: Relevance
“…Rates of testing according to recommended methods, occult blood testing by 3-day kit and SIG, were Ͻ50%, whereas rates of occult blood testing by DRE were higher than expected. These results are similar to other studies that have evaluated CRC screening prevalence using medical record review (22)(23)(24). In a retrospective review of Ͼ5000 medical records, Ruffin et al (22) found rates of FOBT by DRE, FOBT by 3-day kit in the previous year, and SIG in the past 5 years to be ϳ35, 27, and 20%, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Rates of testing according to recommended methods, occult blood testing by 3-day kit and SIG, were Ͻ50%, whereas rates of occult blood testing by DRE were higher than expected. These results are similar to other studies that have evaluated CRC screening prevalence using medical record review (22)(23)(24). In a retrospective review of Ͼ5000 medical records, Ruffin et al (22) found rates of FOBT by DRE, FOBT by 3-day kit in the previous year, and SIG in the past 5 years to be ϳ35, 27, and 20%, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…If specific symptoms were listed leading to the test, the test was considered diagnostic. Because previous studies have not clearly distinguished between tests done for screening versus diagnosis or follow-up (18,19,(22)(23)(24), we used receipt of CRC tests for any reason as our primary outcome (i.e., FOBT by DRE in past year, FOBT by 3-day kit in past year, SIG in past 5 years, and COL in past 10 years). However, we also evaluated receipt of FOBT by 3-day kit or SIG in the past 5 years, excluding tests that were not done specifically for screening.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations